Intra‐operative predictors of postoperative Takotsubo syndrome in liver transplant recipients—An exploratory case‐control study. Issue 11 (14th September 2017) - Aniskevich, Stephen; Chadha, Ryan M.; Peiris, Prith; Taner, Cemal Burcin; Torp, Klaus L.; Thomas, Colleen S.; Yataco, Maria L.; Pai, Sher‐Lu
Abstract: Introduction: Takotsubo syndrome (TTS), also known as Takotsubo cardiomyopathy or stress‐induced cardiomyopathy, has been described following a variety of surgeries and disease states. The relationship between intra‐operative anesthesia management and the development of this syndrome has never been fully elucidated. Objectives: The primary objective of this study was to determine the relationship of multiple intra‐operative factors on the pathogenesis of TTS. Methods: A single‐center retrospective review of all liver transplants performed at Mayo Clinic Florida from January 2005 to December 2014. Patients developing left ventricular dilation and a concomitant decrease in ejection fraction, a negative cardiac catheterization, or stress test within 30 days of transplantation were identified. Cases were matched 2:1 to controls with respect to MELD, age, sex, and indication for transplantation. Our evaluation included liver graft characteristics, intra‐operative medications, and intra‐operative hemodynamic measurements. Results: We identified 24 cases of TTS from a pool of 1752 transplants, for an incidence of 1.4%. No statistically significant differences in intra‐operative measures between the two groups were identified (all P ≥ .08). Conclusion: Our exploratory, single‐center retrospective review evaluating 46 intra‐operative characteristics found no association with the development of TTS.